Riset Pasar Produk Piemirsa (Pie Intip Rasa-rasa) - Anjarsari, Novita Puput, Siti Nandiroh, ST. M.Eng (2017)
The amount of business competition both small-scale enterprises, medium and large businesses require to implement the marketing strategy, not least in the field of culinary. Futher more the need for market research to determine the strengths and weaknesses of the product (brand image) that will be used to apply the right strategy in order to compete in the market. The products studied were PIEMIRSA (Pie Intip Rasa-rasa) is one of the traditional snacks communities Solo. The purpose of this study to obtain results in the form of analysis and interpretation of market research data on potential and market interest in the product Piemirsa and gain strategies to improve product competitiveness. In determining the marketing strategy carried out three analyzes. First of all, analysis of the trend is the result that women prefer shopping for souvenirs than men. Second is similarity analysis, that showed both men and women like piemirsa. The third analysis is odd groupings that can be seen that the majority of respondents liked the voyeur with a variety of flavors. It can be concluded that Piemirsa worth it as the food souvenirs of Solo.